Gene Editing with CRISPR-Cas9 Technology for Hepatitis B Virus: A Literature Review - Rattu, Ferencia (Universitas Sam Ratulangi, 2025)
Hepatitis B Virus (HBV) is a global problem with a significant impact on morbidity and mortality rates that are expected to continue to increase if no further treatment is carried out. HBV is caused by the Hepatitis virus type B, which until now has no medical therapy that can eliminate HBV. The latest developments referring to gene editing for genetic and non-genetic diseases are clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9. CRISPR-Cas9 appears with a promising approach with solutions to various disease disorders. CRISPR-Cas9 with DNA editing by Cas9 endonuclease, which is guided by the RNA sequence is able to pair with the target base sequence. The purpose of this paper is to examine the effectiveness and potential of the gene editing method with CRISPR-Cas9 as a therapy for Hepatitis B disease. The writing method is a Literature Review with databases obtained through Google Scholar, PubMed, and ScienceDirect. Various studies and methods have been developed to improve the success of CRISPR-Cas9. Off-target effects are detected to reduce the risk of CRISPR-Cas9. The results show that CRISPR-Cas9 can inhibit HBV replication in vitro and in vivo. Therefore, the technology shows much-needed potential for eradicating the hepatitis B virus. However, further studies are needed to determine its safety and effectiveness as a hepatitis B therapy.